Boosted microwave absorption properties of CoFe2O4 with extraordinary 3D morphologies. Issue 10 (15th May 2022) - Jiang, Peng; Xu, Qiang; Tran, Ngo; El-Shafay, A.S.; Mohanavel, V.; Abdelrahman, Anas; Ravichandran, M.
Abstract: Due to their strong magnetic dissipation and low cost, ferrites were one of the first generations of microwave absorbers. However, ferrites also have some drawbacks, such as a low natural resonance frequency ( f r ), a lack of dielectric loss, and high density. In order to overcome these drawbacks and improve the microwave dissipation features of ferrites, we successfully prepared CoFe2 O4 samples with flower-like and crochet ball-like morphologies (named as M1 and M2 samples, respectively). Structural and optical properties were studied by XRD, FTIR, and UV–Vis light absorption. The microwave performance of CoFe2 O4 was significantly improved with the reflection loss (RL) of M2 of −40 dB. Furthermore, M1 and M2 samples achieved an ultra-wide effective absorption bandwidth (EAB) of 13 and 12.5 GHz, respectively. It is worth noticing that the EAB of M1 was one of the largest EABs for CoFe2 O4 that has been reported so far. The excellent microwave dissipation of M1 and M2 samples in the 2–18 GHz frequency range was due to the enhancement of ferrite f r to the high-frequency range and the introduction of dielectric loss to achieve impedance matching. The flower-like and crochet ball-like morphologies with many pores of M1 and M2 also resolved the high-density issue of CoFe2 O4 . With the relatively good values of RL and EAB combined with low filler loading, thin thickness, and low density, M1 and M2 samples could be expected to be promising microwave absorbers for practical applications.